Mathematical modelling of working process of the bridge crane with relay drives of the bridge and cargo cart - V. S. Scherbakov; M. S. Korytov; E. O. Shershneva (Вестник СибАДИ, 2017)
The algorithm of modelling of working process of the bridge crane taking into account dynamic parametres of drives of the bridge and the cargo cart, having managements of relay type is resulted. Results of research of influence of parametres of drives of the bridge crane on accuracy of moving of cargo on the set trajectory in three-dimensional space, final linear speed of movement of cargo, number of inclusions of drives are resulted. The received mathematical models open possibility of synthesis of parametres of drives of the bridge crane on the set limiting values of accuracy of movings, numbers of inclusions of drives, etc.